2021
DOI: 10.31004/jkt.v2i2.1784
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Kepatuhan Konsumsi Tablet Tambah Darah Dengan Kejadian Anemia Pada Remaja Putri: A Systematic Review

Abstract: Pada usia remaja, gizi merupakan salah satu masalah yang masih terjadi. Tingkat kejadian di Indonesia sebesar 7,5 juta dan memasuki angka 8 dari 11 negara di Asia. Kejadian ini lebih sering terjadi pada remaja putri karena mempunya siklus menstruasi. Status anemia pada remaja diduga dipengaruhi oleh beberapa faktor yaitu pengetahuan gizi serta kepatuhan konsumsi tablet tambah darah. Tujuan adanya penelitian ini untuk menganalisis hubungan antara kepatuhan konsumsi tablet tambah darah dengan kejadian anemia pad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 6 publications
(13 reference statements)
0
9
0
5
Order By: Relevance
“…The low adherence to the consumption of iron tablets is related to the incidence of anemia cases in adolescent girls. (Savitri et al, 2021). Several factors aff ect adherence to iron tablets in adolescents, namely sociodemographic, cues to action , intrapersonal, interpersonal, and institutional factors.…”
Section: Resultsmentioning
confidence: 99%
“…The low adherence to the consumption of iron tablets is related to the incidence of anemia cases in adolescent girls. (Savitri et al, 2021). Several factors aff ect adherence to iron tablets in adolescents, namely sociodemographic, cues to action , intrapersonal, interpersonal, and institutional factors.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the previous study found that all students had received blood supplement packages for free, but not all students spent their blood supplement tablets due to nausea and dislike of the smell or taste of the blood supplement tablets (Widiastuti & Rusmini, 2019). In fact, there is a significant relationship between compliance with the consumption of tablets added blood with the incidence of anemia in adolescent girls, that the more compliant in consuming tablets added blood then the levels of HB adolescent girls will increase (Savitri et al, 2021). The community empowerment increase opportunities, participation, and access to health services of women in their household and community (Aprillia et al, 2023).…”
Section: B Behaviormentioning
confidence: 96%
“…Oleh karena itu, hal tersebut akan mengakibatkan intake nutrisi tidak adekuat dan janin akan mengalami keterlambatan perkembangan (Restiana & Fadilah, 2023). Para kader kesehatan biasa akan menyarankan para calon orang tua untuk mengonsumsi tablet tambah darah untuk menurunkan kejadian stunting pada anak yang dilahirkannya yang diinformasikan sejak remaja (Savitri et al, 2021). Usia yang disarankan adalah antara 21-35 tahun untuk mengandung (Restiana & Fadilah, 2023) agar terhindar dari berbagai macam masalah fisik maupun psikologis (Hanum & Tukiman, 2015).…”
Section: B Pembahasanunclassified